2010
DOI: 10.2967/jnumed.109.073833
|View full text |Cite
|
Sign up to set email alerts
|

PET Assessment of Myocardial Perfusion Reserve Inversely Correlates with Intravascular Ultrasound Findings in Angiographically Normal Cardiac Transplant Recipients

Abstract: Cardiac allograft vasculopathy (CAV) is the major determinant of long-term survival after heart transplantation. We aimed to evaluate the efficacy of PET as a noninvasive way to assess the early stages of CAV. Methods: Twenty-seven consecutive patients (20 men and 7 women; mean age 6 SD, 46 6 12 y) who had normal results on coronary angiography and normal left ventricular systolic function (ejection fraction $ 60%) were enrolled at 2.5 6 2.1 y after transplantation. Myocardial blood flow (MBF) was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…CI, confidence interval. mined on IVUS agrees well with myocardial perfusion reserve assessed on PET in OHT recipients, 12 it can be used as a marker of inducible ischemia burden and disease severity. In the present study, QTc on ECG and MCG was significantly higher in OHT patients than in those with patent coronary angiogram (both P<0.0001), but did not correlate well with any IVUS parameters.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…CI, confidence interval. mined on IVUS agrees well with myocardial perfusion reserve assessed on PET in OHT recipients, 12 it can be used as a marker of inducible ischemia burden and disease severity. In the present study, QTc on ECG and MCG was significantly higher in OHT patients than in those with patent coronary angiogram (both P<0.0001), but did not correlate well with any IVUS parameters.…”
Section: Resultsmentioning
confidence: 56%
“…For each subject, namic perfusion positron emission tomography (PET) has been considered superior to invasive coronary angiography and SPECT in the detection of CAV. 12 The complexity of production and delivery of short-lived PET tracers, high cost and radiation exposure, however, hinder wide utilization. Therefore, the need for a sensitive and non-invasive surveillance diagnostic tool is of clinical importance.…”
Section: Subjectsmentioning
confidence: 99%
“…As well as myocardial perfusion reserve, perfusion of the epicardial arteries and the microvasculature can be determined [85,86] . In patients after heart transplantation, myocardial perfusion reserve measured with PET has been performed in a few studies [87][88][89] . Wu et al [88] found good correlation between IVUS and myocardial perfusion reserve even in the absence of angiographic lesions.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…In patients after heart transplantation, myocardial perfusion reserve measured with PET has been performed in a few studies [87][88][89] . Wu et al [88] found good correlation between IVUS and myocardial perfusion reserve even in the absence of angiographic lesions. Published data is very limited even in adults, related to the limited availability of the technique and the expertise required.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…16 PET, while expensive and not widely available, may also quantify myocardial blood flow and can demonstrate early CAV in patients who have angiographically normal coronary arteries. 17 If the purpose of the test is to evaluate for severe CAV which would mandate angiography and revascularization, gated SPECT appears to be sufficiently sensitive, and the high negative predictive value of a normal test may safely allow delay or decrease in frequency of angiograms in the short term. If the purpose is to assess overall prognosis, for example for clinical trials, gated SPECT integrates macrovascular, microvascular, and functional data and provide information not available from CAG.…”
mentioning
confidence: 99%